A Field Study on Political Socialization of Political Science Students - Ali Çiçek (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Political socialisation refers to a process in which every individual who is born into society learns the basic values, institutions and rules of the society into which it is born and becomes compatible with the political culture. In this process, the individual learns the boundaries of their own society unconsciously, the roles in that society, the forms of behaviour deemed legitimate and political beliefs. In political socialisation as a learning process, institutions such as family, friendship networks, school, mass media and religion have constructive and transformative roles in the process. Political socialisation processes of individuals are shaped by these institutions worldwide. This study claims to reveal the factors affecting the political socialisation processes of political science students in Türkiye. The field research part of the study was carried out with quantitative research methods and survey design. In this context, a survey was administered to 426 students who continue their education in the department of political science in Türkiye. The hypotheses determined for the study were tested by analysing the survey data in the SPSS package programme. The findings of the study show that students who continue their undergraduate education in political science in Turkey frequently discuss politics with their families, but their families do not want to support their children in joining a political organisation. Political science students do not respond favourably to invitations from their friends to attend political meetings, and although they frequently follow politics through mass media, they avoid interacting even online platforms. In addition, the hypotheses of the study show that there is a significant relationship between political socialisation and gender and political ideology.